Study of mononchids from Iran, with description of Mylonchulus kermaniensis sp. n. (Nematoda: Mononchida) - Shokoohi, Ebrahim; Mehrabi-Nasab, Abdolrahman; Mirzaei, Mahdieh; Peneva, Vlada (Zootaxa, 2013)
During a survey of soil nematodes in Iran, three species of predatory nematodes, including a new species of the genus Mylonchulus Cobb, 1916 were recovered. Mylonchulus kermaniensis sp. n. is characterised by its body length (1.2–1.4 mm), six rows of rasp-like denticles, the sixth line consisting of four denticles, female tail slightly sigmoid, sharply bent ventrad with digitate posterior portion slightly but clearly bent dorsad, (37–49 μm long, c=27.9–38.9, c'=1.2–1.7) with a terminal opening of spinneret. Two advulval papillae present, one is pre-vulval and the other one is located posterior to vulva. Furthermore, two other mononchid species namely M. cf. hawaiiensis (Cassidy, 1931) Goodey, 1951 and Mononchus truncatus Bastian, 1865 were also recovered from soil in the province of Kerman, Iran, the former representing a new geographical record for Iran. Measurements and illustration are provided for these three species. Molecular study of 18S rDNA region of M. cf. hawaiiensis demonstrated that the Iranian population compared with the nearest populations identified as M. hawaiiensis from Japan, shows 5 to 8 nucleotide differences. In addition, phylogeny of Mylonchulus is discussed and a checklist of the species of Mononchida from Iran is provided.